Conditional Handicaps in Exuberant Lizards: Bright Color in Aggressive Males Is Correlated with High Levels of Free Radicals - Friesen, Christopher R.; Wilson, Mark R.; Rollings, Nicky; Sudyka, Joanna; Whittington, Camilla M.; Giraudeau, Mathieu; Olsson, Mats (Frontiers in Ecology and Evolution, 2017)
The maintenance of genetic variation and signal honesty may be explained, in part, through the genic capture hypothesis in sexual selection biology. Polygenic traits, like body condition, could help maintain variation in signaling traits under strong, directional sexual selection while maintaining signal honesty. Here we consider the genic capture hypothesis in a study of morph-specific condition and free radical effects on signaling traits (head coloration) in males of a polymorphic lizard, the Australian painted dragon (Ctenophorus pictus). Males differ in head color (red, orange, yellow, and a “blue” morph that has no yellow or red pigments). The red and yellow morphs were the first described and we have previously demonstrated that red morphs are aggressive and dominant over yellow morphs that are better at sperm completion than the red morphs. Body condition varied significantly in its relationship with superoxide among the four morphs, with males in better condition showing higher superoxide levels in “yellow-orange-reds” morphs (least so in red morphs). Blue morphs contrasted markedly by showing lower superoxide levels in males in better condition, perhaps facilitated by no (or reduced) dermal deposition of pigmentation on the head. Color degradation with loss in condition from yellow to red morphs, suggesting that red morphs are better able to maintain color with superoxide acting as a potential handicap. This result is consistent with condition-dependent signal expression and the genic capture hypothesis; males with the more pronounced signal carry a higher potential cost (higher superoxide levels) when being in better body condition, while maintaining more vivid coloration (the condition-dependent trait).